Chemically interconnected amorphous nanospheres SiOxCy as high performance anodes. (10th September 2022) - Ouyang, Quan; Li, Guangshe; Liu, Xiaoqing; Wang, Qiao; Zhang, Xin; Wang, Jiaxin; Fan, Zhipeng; Gao, Guichen; Li, Liping
Abstract: Lithium battery, equipped with SiOx as anode, can deliver high discharge capacity, compared to conventional graphite anode. The application of SiOx in the lithium battery, however, is challenging due to its low conductivity and large volume expansion. In this study, a new sol-gel copolymerization route in free of toxic solvent is designed to synthesize interconnected amorphous SiOx Cy (x∼1.5, 1.1≤y≤3.1) nanospheres. Both carbon and silica are chemically intertwined via Si-C and Si-O-C bonds, showing a homogeneous distribution throughout amorphous spheres at the atomic scale. These amorphous spheres are cemented through interfacial junctions, thereby forming the continuous electron transport passages. We discover that such amorphous spheres have a specific area of 16 m 2 /g, the lowest value currently reported. When used as lithium battery anode, chemically interconnected amorphous nanospheres show an excellent electrochemical performance, as represented by a reversible capacity as high as 697 mAh/g at a current density of 0.5 A/g after 500 cycles, which is superior to those ever reported in literature. The methodology reported here opens a potential avenue to develop chemically interconnected multi-component amorphous nanospheres with tunable chemical bonding states and conductive interfaces for different applications.